2020
DOI: 10.1158/1078-0432.ccr-19-3529
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DNA Damage Response and Repair (DDR) Gene Mutations on Efficacy of PD-(L)1 Immune Checkpoint Inhibition in Non–Small Cell Lung Cancer

Abstract: Impact of DNA damage response and repair (DDR) gene mutations on efficacy of PD-(L)1 immune checkpoint inhibition in non-small cell lung cancerRunning Title: DDR gene mutations and immunotherapy efficacy in NSCLC.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
116
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 45 publications
12
116
1
Order By: Relevance
“…harboring mutations in DDR genes had longer progressionfree survival and overall survival under an ICI treatment (Ricciuti et al, 2020).…”
Section: Potential Regulation Of Neoantigen Production In Dna Damage mentioning
confidence: 99%
See 1 more Smart Citation
“…harboring mutations in DDR genes had longer progressionfree survival and overall survival under an ICI treatment (Ricciuti et al, 2020).…”
Section: Potential Regulation Of Neoantigen Production In Dna Damage mentioning
confidence: 99%
“…The result of the database analysis is supported by a recent study by Cheng’s group, which reported that the analysis of tumor samples from patients with non-small cell lung cancer treated with anti-PD-1/PD-L1 antibody using next-generation sequencing revealed that patients with DDR mutation (the most commonly mutated DDRs were ATM , ATR , BRCA2 , POLQ , and RAD50 in the analysis) exhibited high TMB. The patients harboring mutations in DDR genes had longer progression-free survival and overall survival under an ICI treatment ( Ricciuti et al, 2020 ).…”
Section: Potential Regulation Of Neoantigen Production In Dna Damage mentioning
confidence: 99%
“…The FANCA gene is important for the repair of double-stranded DNA breaks and is involved in the cellular process known as the Fanconi anemia pathway. Outcomes have been assessed in patients treated with ICIs, and the results showed significantly higher objective response rate, longer median PFS, and longer median OS with patients on PD-(L)1 therapy [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, activating of oncogenic signaling pathways like PI3K-AKT-mTOR pathway, Jak-STAT pathway and KRAS-ERK pathway, can also induce PD-L1 expression in NSCLC or other cancer types [17][18][19]. Recently, NSCLC patients with driver gene mutation in DDR pathways presented signi cant higher TMB values and higher objective response rate, longer median PFS, showing improved clinical responses to anti-cancer immunotherapy in NSCLC [32].We also found DDR pathway, TP53 pathway, cell cycles pathway and NOTCH pathway were highly correlated with high PD-L1 expression in Chinese lung adenocarcinoma patients (P < 0.05), which might provide more evidences for illustrating a clearer molecular mechanism for PD-L1 expression in Chinese patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%